Effect of plyometric training on explosive strength in team sports: a meta-analysis - Alfaro Jiménez, Denis Francisco (2018)
Plyometric training (EPLI) is used to improve explosive actions in many sports; however, this training does not generate the same effect in all sports. The purpose of the study was to evaluate the effect of plyometric training on explosive strength (FE) in team sports. In the final analysis, 31 studies were included generating 50 Effect Sizes (ES). Under a random effects model, the EPLI was found to be effective in improving FE (ES=0.98, p=0.00, CI95%=0.77 to 1.20, n=50, Q=174.51, I²=71.95) in team sports. Results indicate that, in order to improve FE in this type of sports, plyometric training should be used without combining it with other types of exercises for at least ten weeks. In addition, this training improves jump height in both the preparatory as well as the competitive periods, regardless of the type of protocol used. The results of this meta-analysis should be used in confirmatory studies including other sports.  In addition, this topic should be further studied in women, as well as the combination between EPLI with other types of excercises and trainings.